Evaluation of Pre-Transplant Panel Reactive Antibody Levels and Sensitization: A Single-Center Study - (:unkn) unknown (INT SCIENTIFIC LITERATURE, INC, 2016)
Background: Sensitization is one of the most important barriers against transplantation. Our aim was to evaluate the sensitization status of our patients awaiting cadaveric transplantation and to identify factors causing sensitization. Material/Methods: A total of 140 patients on the cadaveric waiting list during January 2014 were included in this retrospective cross-sectional study. The parametric t-test and the non-parametric chi-square test were used to detect differences between PRA-positive and -negative patients. Multivariate analysis was used to identify factors associated with PRA positivity. One-way analysis of variance was used to compare PRA-negative and -positive results. Results: Anti-HCV positivity (p=0.040), history of transfusion (p=0.041), and mean number of blood product transfused (p=0.047) were significantly related to class 1 PRA positivity. History of transfusion (p=0.038) and mean number of blood product transfused (p=0.044) were related to class 2 PRA positivity. The multivariate analysis indicated that transfusion and more than 5 units of blood product transfused were related to either class 1 or class 2 PRA positivity. No associations were found between PRA positivity and pregnancy, transplantation, age, sex, infection, abortion, cardiovascular disease, diabetes mellitus, hepatitis B, or time spent on dialysis and being on the transplantation waiting list. Conclusions: Anti-HCV positivity and transfusion are risk factors for sensitization. Particular emphasis should be given to sensitization and its prevention to reduce waiting time for transplantation.
Keywords: Blood Transfusion; Hepatitis C Antibodies; HLA Antigens; Kidney Transplantation; Waiting Lists; KIDNEY PAIRED DONATION; RENAL-TRANSPLANTATION; HEPATITIS-C; SURVIVAL; DESENSITIZATION